Produtividade e qualidade fisiológica de sementes de erva-doce em função da adubação orgânica e mineral e de sistemas de cultivos - Moura, Mácio Farias de (2007)
The effects of the cattle manure on either yield and physiological quality of the anise seeds were studied during the period from April 2005 to July 2006, in the Universidade Federal da Paraíba, Areia -PB. Cattle manure at the doses 0, 5, 10, 15 and 20 t. ha-1 were used under the absence and presence of the mineral fertilization. The following cropping systems were adopted: single and associated with sweet potato, maize and caupi-bean. The following associate crops were used: sweet potato (Rainha Branca cv.), maize (Hybrid AG - 1051) and caupi bean (IPA 206 cv.). The anise seedlings with 20cm average height were transplanted into four rows with eight plants, so totaling 32 anise plants in each plot at spacing 1.50 x 1.00m, and those located among the associate crops were evaluated. The following characteristics were appraised: plant height, number of primary and secondary umbels per plant, seed yield, water content, plantlet emergency, first emergency counting, emergency speed index (IVE), root length and the aerial part length. The randomized block experimental design was used, whereas the treatments were distributed under split-plot arrangement, with three replicates. The plant height was reduced as a function of the cattle manure dose and at the presence of mineral fertilization in the single cropping system. The maximum values of the primary and secondary anise umbels were 19 and 138.4 at the doses 10.1 and 11.2 t. ha-1 cattle manure, respectively, with mineral fertilization in the anise associated with maize. Productivity reached the highest value (156.8 kg ha-1) in the single cropping system and mineral fertilizer. The plantlet emergency attained the highest percentages (88.8%), when applying 5.8 t. ha-1 cattle manure, without mineral fertilization, in anise associated with caupi bean. In consortium of the anise with sweet potato, some 20 t. ha-1 cattle manure and mineral fertilization provided the highest values at the first emergency counting (83%), emergency speed index and root length. The maximum length of the aerial part was obtained with the application of 10.9 t. ha-1 cattle manure, without mineral fertilization in the cropping system of anise with caupi bean.